FACULTY OF SPORT SCIENCE UNIVERSITAS NEGERI JAKARTA 2014 - Tangkudung, James; Wardoyo, Hendro (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2016)
The purpose of this study was to determine the physical conditions owned student Achievement Sports Club Students of Pencak Silat (Koppensi) Faculty of Sport Science that in terms of the condition of endurance, strength, velocity, and flexibility. This study was conducted in faculty of Sport Science, State University of Jakarta, using descriptive methods, and techniques used in this research is the analysis of the documentary, which took secondary data test results biomotor conditions. The results of the study for male athletes (members) to test the physical condition endurance aspect, the velocity of male athlete shows the time 3.15 seconds; For the average male athlete flexibility 28 cm; For endurance athletes arm and shoulder muscles son is 34 times. The average male athlete arm muscle strength was 42.5 kg. For female athletes (members) have results of physical condition tests for endurance aspects, 42.5 cc / kg / minute; female athletes showed a speed of 4.11 seconds; flexibility female athlete of 24 cm; muscular endurance athletes arms and shoulders of women is 12 times. The average female athletes arm muscle strength is 33.3 kg.